THE TEACHING SPEAKING IN â€œSPEAK FIRST CLASSâ€ OF THE DAFFODILS ENGLISH COURSE PARE - Nenghayah, Siti; Purwantoro, Purwantoro (LENTERA : Jurnal Pendidikan dan Pengajaran; Vol 9 No 2 (2019): LENTERA : Jurnal Pendidikan dan Pengajaran, 2019)
This research is aimed to describe and to get result of the teaching speaking by using chatting in pair of Speak First Class of The Daffodils English Course Pare. Those are including of  the teachersâ€™ preparation in teaching speaking, lesson materials in teaching speaking using chatting in pair, the implementation of teaching speaking using chatting in pair evaluation used, the problem of teaching speaking using chatting in pair, and also know the studentsâ€™ speaking skill.. This research used descriptive qualitative as a research design. The subject was 20 students of the Speak First Class.  The methods used in collecting data were participant observation, interview, documentation, and test. The model of teaching is students pairing. The data analysis was based on three concurrent flows of activities, they were: data reduction, data display, verification and triangulation. That is found that based on the researcher, the speaking skill of the students is in good category. That is seen from 0% from 20 students in excellent level, 35 % in very good level from 20 students, thatâ€™s 7 students, 65% in good level from 20 students, thatâ€™s 13 students, 0% in average level and 0% in poor level